Propensity score matched all comers population treated with ultra‐thin strut bare metal and sirolimus‐probucol coated drug‐eluting stents of identical stent architecture. Issue 7 (25th September 2017) - Krackhardt, Florian; Rosli, Mohd Ali; Leschke, Matthias; Schneider, André; Sperling, Christian; Heang, Tay Mok; Pons, Maxime; Sousa, Pedro Jerónimo; Kherad, Behrouz; Waliszewski, Matthias
Abstract: Objective: The objective of this study was to compare the safety and efficacy of a polymer‐free sirolimus coated, ultrathin strut drug eluting stent (PF‐SES) to its uncoated bare‐metal stent (BMS) platform of identical stent architecture. Background: Recently published randomized trials comparing BMS to DES with a focus on shortened dual‐antiplatelet therapy reported incidences of stent thrombosis (ST) and bleeding complications (LEADERS FREE) in favor of drug eluting stents (DES). Methods: Data of previously published large‐sale, international, single‐armed, multicenter, observational studies of ultra‐thin PF‐SES, and BMS were propensity score (PS) matched for selected lesion morphological and cardiovascular risk factors to compare target lesion revascularization (TLR), myocardial infarction, cardiac death, major adverse cardiac events (MACE), bleeding complications and ST rates. Primary endpoint in both studies was TLR at 9 months. Results: At 9 months the rates of TLR was significantly lower in the PF‐SES group as compared with patients treated with the BMS analogue of identical stent design (1.4% vs. 4.6%, P  = 0.005). Likewise the 9‐month MACE rates were lower in the PF‐SES group (3.2% vs. 8.7%, P  = 0.001) whereas there were no differences in the accumulated ST rates (0.5% vs. 1.5%, P = 0.109). Overall accumulated bleeding incidences (BARC 1–5) were not significantly different between PF‐SES and BMS patients (1.8% vs. 2.7%, p  = 0.388). Conclusions: PF‐SES are superior over analogue BMS of identical stent architecture in daily clinical routine with lower rates of TLR and MACE in a PS‐matched, unselected patient population without differences in accumulated ST rates and bleeding frequencies given the currently favored postprocedural comedication (ClinicalTrials.gov Identifier NCT02629575).